The Effect of Call Center Service Quality On Outpatient Satisfaction Level At St. Carolus Hospital Jakarta - Novita Eka Putri, Yosephine; Adrian, Adrian; Marpaung, Oktavia (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
This study aims to analyze The Effect of Call Center Service Quality on Outoutpatient Satisfaction Levels at St. Carolus Hospital Jakarta. The variables studied are Service Quality (Reliability (X1) and Assurance (X2)) and Outoutpatient Satisfaction (Y). The type of research used is the type of research, and the type of data is primary. The technique of collecting research data is through the questionnaire method. Furthermore, the sampling technique used is purposive sampling with 75 respondents. Data analysis in this study used SPSS version 25. The analysis used in this research is a validity test, reliability test, multicollinearity test, heteroscedasticity test, normality test, multiple linear analysis, correlation coefficient analysis test t test, F test, and coefficient of determination (R2). The results of testing and analysis of this study show that the Assurance variable has a significant influence with a sig value of 0.000 <0.05, a t-count value of 4.336 > t-table, and a beta (β) value of 0.308, so it can be concluded that the Assurance variable (X2) has a significant influence significant to the dependent variable (Y), namely outpatient satisfaction.